Glass beads as identity element of the African in the cultural past of Lisbon from the mid XV century until the 1755 earthquake - Rodrigues, M. Conceição (Zephyrvs, 2009)
ABSTRACT: This paper is centred in the study of long glass beads, which can be considered as an identity element of some African communities. They were brought to Lisbon by slaves through the commercial routes developed between Portugal and the South Western African Coast, since the middle of the XV century. The studied specimens came from the archaeological interventions carried out in the Lisbon downtown, of the period prior to the 1755 earthquake, in the end of the 1990’s. Among them are some “Nueva Cadiz” beads, as well as “Chevron” beads and the former deserved special mention, since they are a Mediterranean manufacture. The author did similar studies of other beads, which were used as comparative elements in this paper. These beads mirror some of the events and socio-cultural aspects of the life of Africans in Lisbon since the XV century until the 1755 earthquake. Beads were used as a distinguishing element and a social valorisation. Through technical-morphological and mineralogical studies a connection between them and historical data is attempted. RESUMO: Este nosso trabalho centra-se no estudo de contas longas de vidro que consideramos ser um elemento identitário de algumas das comunidades africanas que foram trazidas como escravos, através das rotas comerciais desenvolvidas entre Portugal e a costa Ocidental da África Austral, desde meados do século XV. Os exemplares aqui em estudo são um dos elementos materiais fornecidos como resultado das intervenções arqueológicas na Lisboa anterior a 1755, e que tiveram lugar nos finais da década de 90 do século XX. Vamos procurar efectuar o estudo de um núcleo de contas de vidro, entre as quais se encontram as de cor azul tipo “Nueva Cadiz” e as contas “Chevron ou em Estrela” que apresentam várias tonalidades. As primeiras mereceram uma atenção particular por se enquadrarem num tipo de contas de fabrico mediterrânico, cujo estudo vimos desenvolvendo desde os inícios dos anos 90. Como metodologia, os exemplares que anteriormente estudámos irão servir como elemento de comparação. Importa ainda enquadrar a sua presença nos acontecimentos e vivências socio-culturais dos africanos na Lisboa do século XV até ao terramoto de 1755, dado terem sido usadas como elemento de identidade para a sua valorização social, além de efectuarmos o seu estudo técnico-morfológico e mineralógico. Procurou-se ainda, estabelecer a ligação entre este tipo de elementos materiais e os dados históricos.